The Effectiveness of Implementation of Permenkes Number 10 Year 2021 Concerning Implementation of Vaccines for Management of COVID-19 in The Community - Nura Damayanti Ariningsih; Windy Ratna Yulifa (Journal Research of Social Science, Economics, and Management, 2021)
Minister of Health Regulation Number 10 of 2021 concerning Vaccines in the Context of the Covid-19 Pandemic, in the regulation it is stated in Article 1 Number 1 concerning the definition of vaccines, vaccines are biological products that contain antigens in the form of dead or attenuated live microorganisms, still intact. or part thereof, or in the form of a microorganism toxin that has been processed into a toxoid or recombinant protein, which is added with other substances, which when administered to a person actively causes specific immunity against certain diseases. The fact on the ground is that currently the Covid-19 vaccine program is faced with various reasons for acceptance and rejection related to this. The problem in this study is how to implement Permenkes No. 10 of 2021 regarding the implementation of vaccinations in the context of controlling COVID-19 in the community and how the community responds to vaccinations in Indonesia. This research method is juridical-empirical by collecting data through questionnaires to determine the effectiveness of the implementation of Minister of Health Regulation Number 10 of 2021 concerning Vaccines in the Context of Corona Virus Disease 2019 (Covid-19) in the Community. Based on the results of the study, it was concluded that the implementation of Ministerial Regulation Number 10 of 2021 concerning Vaccines in the Context of the Corona Virus Disease 2019 (Covid-19) Pandemic in the community has received a lot of approval regarding the Covid-19 vaccine program policy because the program aims to stem the Covid pandemic. -19 this.